2021
DOI: 10.1093/cid/ciaa1933
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Encephalitis Is a Cytokine Release Syndrome: Evidences From Cerebrospinal Fluid Analyses

Abstract: Background Recent findings indicated that SARS-CoV-2 related neurological manifestations involve cytokine release syndrome along with endothelial activation, blood brain barrier dysfunction, and immune-mediated mechanisms. Very few studies have fully investigated the CSF correlates of SARS-CoV-2 encephalitis. Methods Patients with PCR-confirmed SARS-CoV-2 infection and encephalitis (COV-Enc), encephalitis without SARS-CoV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 151 publications
(179 citation statements)
references
References 31 publications
8
166
1
4
Order By: Relevance
“…Furthermore, cognitive impairment with prominent decline in executive functions has been reported in COVID-19 patients, either in the acute phase, or at discharge, and correlates with COVID-19 disease severity and use of mechanical ventilation [2,5,6]. Presence of inflammatory markers in serum and/or cerebrospinal fluid (CSF), such as increased interleukin 6 (IL-6), IL-8, or oligoclonal bands, have been reported by several groups in association to this clinical phenotype [2][3][4]7]. Frontal abnormalities on electroencephalography (EEG), including slowwaves and slowing-down of the background rhythm or epileptiform discharges, are present in one-third of COVID-19 patients and have been proposed as an EEG biomarker for COVID-19 encephalopathy [8].…”
Section: Clinical Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, cognitive impairment with prominent decline in executive functions has been reported in COVID-19 patients, either in the acute phase, or at discharge, and correlates with COVID-19 disease severity and use of mechanical ventilation [2,5,6]. Presence of inflammatory markers in serum and/or cerebrospinal fluid (CSF), such as increased interleukin 6 (IL-6), IL-8, or oligoclonal bands, have been reported by several groups in association to this clinical phenotype [2][3][4]7]. Frontal abnormalities on electroencephalography (EEG), including slowwaves and slowing-down of the background rhythm or epileptiform discharges, are present in one-third of COVID-19 patients and have been proposed as an EEG biomarker for COVID-19 encephalopathy [8].…”
Section: Clinical Evidencementioning
confidence: 97%
“…Indeed, the pattern of activated microglia seems reminiscent of autoimmune encephalitis rather than direct central nervous system (CNS) damage caused by the virus [18]. An inflammatory process could be in keeping with increased levels of glial markers, including fibrillary acidic protein (GFAP), sTREM-2, and YKL-40, found in COVID-19 patients in plasma and in the brain [7,18,24]. COVID-19 encephalitis presenting as Acute Disseminated Encephalomyelitis (ADEM) or limbic encephalitis have also been reported, suggesting a possible, though rarer, autoimmune mechanism [25][26][27].…”
Section: Pathophysiological Theoriesmentioning
confidence: 99%
“…3,9 Additionally, CSF analysis, neuroimaging, and neuropathological findings, as well as the clinical response to various immunotherapies, are not consistent with an infectious disease targeting the brain but rather with an immune-mediated pathogenesis. 4,[9][10][11] Therefore, a cytokine-mediated neuroinflammatory process, associated with cytokine storm, has been suggested as the underlying pathogenic mechanism. 5,10,[12][13][14] Chimeric antigen receptor T-cell (CAR-T) therapy is a novel and highly effective treatment for refractory hematological malignancies, whose most common complication is cytokine release syndrome, a cytokine storm disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our report, two recent studies observed vascular leakage and peri-vascular immune infiltration in the brain of COVID-19 patients, but without the crucial link to ACE2 expression by, and infection of, pericytes 27, 28 . However, it is still an outstanding question whether SARS-CoV-2 is overtly neurotropic or if the neurological symptoms associated with COVID-19 are secondary to events related to the systemic host response 29 . Although solely based on the comparable abundance of GFAP in the tissues, our observations do not provide support for the hypothesis of a cytokine storm.…”
Section: Discussionmentioning
confidence: 99%